Characterisation of Lipid Changes in Ethylene-Promoted Senescence and Its Retardation by Suppression of Phospholipase Dδ in Arabidopsis Leaves - Jia, Yanxia; Li, Weiqi (Frontiers in Plant Science, 2015)
Ethylene and abscisic acid (ABA) both accelerate senescence of detached Arabidopsis leaves. We previously showed that suppression of Phospholipase Dδ (PLDδ) retarded ABA-promoted senescence. Here, we report that ethylene-promoted senescence is retarded in detached leaves lacking PLDδ. We further used lipidomics to comparatively profile the molecular species of membrane lipids between wild-type and PLDδ-knockout (PLDδ-KO) Arabidopsis during ethylene-promoted senescence. Lipid profiling revealed that ethylene caused a decrease in all lipids levels, except phosphatidic acid (PA), caused increases in the ratios of digalactosyl diglyceride /monogalactosyl diglyceride (MGDG) and phosphatidylcholine (PC)/phosphatidylethanolamine (PE), and caused degradation of plastidic lipids before that of extraplastidic lipids in wild-type plants. The accelerated degradation of plastidic lipids during ethylene-promoted senescence in wild-type plants was attenuated in PLDδ-KO plants. No obvious differences in substrate and product of PLDδ-catalysed phospholipid hydrolysis were detected between wild-type and PLDδ-KO plants, which indicated that the retardation of ethylene-promoted senescence by suppressing PLDδ might not be related to the role of PLDδ in catalysing phospholipid degradation. In contrast, higher plastidic lipid content, especially of MGDG, in PLDδ-KO plants was crucial for maintaining photosynthetic activity. The lower relative content of PA and higher PC/PE ratio in PLDδ-KO plants might contribute to maintaining cell membrane integrity. The integrity of the cell membrane in PLDδ-KO plants facilitated maintenance of the membrane function and of the proteins associated with the membrane. Taking these findings together, higher plastidic lipid content and the integrity of the cell membrane in PLDδ-KO plants might contribute to the retardation of ethylene-promoted senescence by the suppression of PLDδ.